INTENSIVE INTRAVENOUS REGIMEN FOR SEVERE ATTACKS OF ULCERATIVE COLITIS - Truelove, S; Jewell, D (1974)
A 5-day intensive intravenous regimen for the treatment of severe attacks of ulcerative colitis has been developed, and the results in forty-nine patients treated in this way in a 5-year period are described. Thirty-six patients were in complete remission at the end of the 5-day course. Four showed clinical improvement without remission, and they all required urgent surgery within the next 6 weeks. The remainder were unchanged by the intravenous regimen and required emergency surgery. This regimen gives a higher remission-rate than has been recorded previously, and failure to respond provides a simple and straightforward indication for surgery without further delay. When used in the treatment of first attacks of the disease, the regimen gives a considerable chance of a prolonged remission. Two-thirds of the first-attack patients who went into remission remained symptom-free during the period of follow-up, which averaged more than 3 years. © 1974.